Anaerobic Reactor for Indonesian Tofu Wastewater Treatment - Adisasmito, Sanggono; Borromeus Rasrendra, Carolus; Chandra, Hengky; Adimas Gunartono, Mohammad (International Journal of Engineering and Technology, 2018)
An Upflow Anaerobic Sludge Blanket (UASB) reactor was used to process liquid wastes from a tofu industry with COD (Chemical Oxygen Demand) 7619 mg/L, pH 4, and TSS (Total Suspended Solid) 1035 mg/L. This work is part of efforts to clean Citarum River in West Java, Indonesia, named as Citarum Harum national program.Â  The liquid Hydraulic Retention Time (HRT) in the reactor was varied from 2, 3, 4, and 5 days and the resulting COD outputs were 6783 mg/L, 6494 mg/L, 5806 mg/L, and 4722 mg/L respectively. The results represented up to 38% in COD reduction. Biogas was produced from the UASB Reactor with the maximum production rate of 1.56 mL/min. The composition of the biogas was methane (56.4% -mole), carbon dioxide (42.7% -mole), and impurities (0.9% -mole) with the Lower Heating Value (LHV) of 20.2 MJ/Nm3.Â Â